Kebertahanan dan Implikasi Tradisi Sinoman Masyarakat Jawa dalam Penguatan Solidaritas Sosial dan Ekonomi Masyarakat Multikultural di Konawe Selatan - Akhmad Marhadi; La Ode Marhini; Rahmat Sewa Suraya; Agus Rihu`; Elmy Selfiana Malik; Shinta Arjunita Saputri (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2023)
This research aims to reveal and to describe the continuation and implication of Javanese community’s sinoman tradition in strengthening social and economic solidarity of multicultural community in Wawoosu village of Konawe Selatan Sub District. This research uses a descriptive qualitative approach, a research aiming to describe in detail the phenomenon relevant to the objective of research. The result of research shows as follows. 1) Sinoman tradition is a tradition belonging to Javanese community that can exist and survive in multicultural society in Wawoosu and even this tradition becomes a shared tradition to all members of society and a space for expressing solidarity regardless different social status, race, political view, and religion. On the other hand, sinoman tradition also can survive because this tradition can be bequeathed hereditarily to all member of Wawoosu society through internal (family) and external (government’s intervention and show) inheritances. 2) This sinoman tradition has an implication to the strengthened social solidarity in multicultural society due to the shared cultural values of each ethnics living in Wawoosu village and shared challenge faced in the multicultural social-cultural reality and territorial condition. In addition, this tradition has an implication to the community’s strengthened economy because this implementation of tradition aims to relieve the burden of the people organizing sinoman tradition in the form of money, food staple, and other produces relevant to the rationale of sinoman tradition implementation.